The Influence of Digital Marketing, Halal Labeling, and Business Capital on Product Sales in Franchise Businesses in Sungai Penuh City: Pengaruh Digital Marketing, Labelisasi Halal dan Modal Usaha Terhadap Penjualan Produk pada Usaha Waralaba di Kota Sungai Penuh - Fiora Febria Harvika; Yogi Ahmad Yani (Journal of Creative Power and Ambition (JCPA), 2026)
This study aims to evaluate the impact of digital marketing, halal labeling, and business capital on franchise business sales in Sungai Penuh City. Quantitative methods were used in this study, involving 30 business respondents. The analysis included validity and reliability tests, classical assumptions, multiple linear regression, and t-tests and F-tests. The results showed that digital marketing had a significant positive impact on business revenue. Meanwhile, halal labeling also had a significant, albeit weak, influence. On the other hand, business capital had a significant but negative impact, indicating that additional capital does not always result in increased revenue if not managed properly. Overall, these three factors significantly influenced business sales, contributing 29.6%. This study emphasizes that increasing business sales requires an integrated approach focused on optimizing digital marketing, utilizing halal labels, and efficient capital management.